Tanshinone IIA and hepatocellular carcinoma: A potential therapeutic drug - Li, Hu; Hu, Pengbo; Zou, Yajun; Yuan, Lijuan; Xu, Yucheng; Zhang, Xiaohui; Luo, Xiaoyan; Zhang, Zhiqiang (Frontiers in Oncology, 2023)
Because of its high prevalence and poor long-term clinical treatment effect, liver disease is regarded as a major public health problem around the world. Among them, viral hepatitis, fatty liver, cirrhosis, non-alcoholic fatty liver disease (NAFLD), and autoimmune liver disease are common causes and inducements of liver injury, and play an important role in the occurrence and development of hepatocellular carcinoma (HCC). Tanshinone IIA (TsIIA) is a fat soluble polyphenol of Salvia miltiorrhiza that is extracted from Salvia miltiorrhiza. Because of its strong biological activity (anti-inflammatory, antioxidant), it is widely used in Asia to treat cardiovascular and liver diseases. In addition, TsIIA has shown significant anti-HCC activity in previous studies. It not only has significant anti proliferation and pro apoptotic properties. It can also play an anti-cancer role by mediating a variety of signal pathways, including phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt)/rapamycin (mTOR), mitogen-activated protein kinase (MAPK), and nuclear factor kappa-B (NF-κB). This review not only reviews the existing evidence and molecular mechanism of TsIIA's anti-HCC effect but also reviews the liver-protective effect of TsIIA and its impact on liver fibrosis, NAFLD, and other risk factors for liver cancer. In addition, we also conducted network pharmacological analysis on TsIIA and HCC to further screen and explore the possible targets of TsIIA against hepatocellular carcinoma. It is expected to provide a theoretical basis for the development of anti-HCC-related drugs based on TsIIA.